2015
DOI: 10.1007/s11693-015-9183-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the differences in metabolic behavior of astrocyte and glioblastoma: a flux balance analysis approach

Abstract: Brain cancers demonstrate a complex metabolic behavior so as to adapt the external hypoxic environment and internal stress generated by reactive oxygen species. To survive in these stringent conditions, glioblastoma cells develop an antagonistic metabolic phenotype as compared to their predecessors, the astrocytes, thereby quenching the resources expected for nourishing the neurons. The complexity and cumulative effect of the large scale metabolic functioning of glioblastoma is mostly unexplored. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Moreover, astrocytes activated 52% of model reactions (Figure 3) and preferentially use a glucose-based metabolism. Our model also shows that glucose is catabolized and constitutively released by astrocytes as lactate without any Pathways Involved in Palmitic Acid Toxicity stimuli similar (Le Foll and Levin, 2016), in agreement with Cakir et al (2007) and Bhowmick et al (2015) whom reported a lactate release rate of 8.9% from the glucose flux in resting conditions (Çakir et al, 2007;Bhowmick et al, 2015). As previously stated, astrocytes in physiological conditions release large amounts of lactate to the extracellular space (Mangia et al, 2009), which can be used by neurons to supply their energetic requirements (Kumar Jha et al, 2016).…”
Section: Healthy Scenario (Basal Conditions)supporting
confidence: 82%
“…Moreover, astrocytes activated 52% of model reactions (Figure 3) and preferentially use a glucose-based metabolism. Our model also shows that glucose is catabolized and constitutively released by astrocytes as lactate without any Pathways Involved in Palmitic Acid Toxicity stimuli similar (Le Foll and Levin, 2016), in agreement with Cakir et al (2007) and Bhowmick et al (2015) whom reported a lactate release rate of 8.9% from the glucose flux in resting conditions (Çakir et al, 2007;Bhowmick et al, 2015). As previously stated, astrocytes in physiological conditions release large amounts of lactate to the extracellular space (Mangia et al, 2009), which can be used by neurons to supply their energetic requirements (Kumar Jha et al, 2016).…”
Section: Healthy Scenario (Basal Conditions)supporting
confidence: 82%
“…While carbon metabolism KEGG pathway was identified for deiminated proteins in both GBM cell lines, KEGG pathway for central carbon metabolism in cancer was identified in LN18 cells only. Carbon metabolism is related to metabolic adaption and growth in GBM [125,126], including in TMZ resistance [127] and in the control of glioma cell transformation to a higher aggressive stage [109]. Roles for post-translational deimination in such metabolic control have not been investigated and may be of relevance as this pathway was prominent for deimination in LN18 cells, which present a more aggressive and chemo-resistant form than LN229 [69].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies to apply genome-scale constraint-based modeling to cancer metabolism, an analysis of brain tumors with this approach is scarce. Only a recent study analyzed GBM with the FBA approach, by using a metabolic model with 147 genes and 12 pathways, without the incorporation of gene expression data (Bhowmick et al, 2015 ). Our work provides a much more comprehensive coverage of brain tumor metabolism.…”
Section: Discussionmentioning
confidence: 99%